1984
DOI: 10.1007/bf03189651
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic effects of altered plasma protein binding of drugs in renal disease

Abstract: The measurement of plasma drug concentrations provides no insight into the relationship between the free and the plasma-protein-bound fractions of drugs. Plasma protein binding may decrease in renal disease due to uremia, hypoalbuminemia, or due to drug interactions. Decreased plasma protein binding leads to an increase in free plasma fraction causing an increase in volume of distribution and a shorter elimination half life. The increase in the apparent volume of distribution and the shorter elimination half l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 58 publications
1
40
1
Order By: Relevance
“…This limitation to our study is important in light of the potential effect of the hypoalbuminemia observed in our patients. Hypoalbuminemia may cause a reduced plasma protein binding of drugs, resulting in a potential increase in drug concentration at the site of action [36,37]. This reduced protein binding may also give rise to accelerated overall clearance of the drug.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This limitation to our study is important in light of the potential effect of the hypoalbuminemia observed in our patients. Hypoalbuminemia may cause a reduced plasma protein binding of drugs, resulting in a potential increase in drug concentration at the site of action [36,37]. This reduced protein binding may also give rise to accelerated overall clearance of the drug.…”
Section: Discussionmentioning
confidence: 97%
“…This reduced protein binding may also give rise to accelerated overall clearance of the drug. These two potential mechanisms often offset each other and render the influence of hypoalbuminemia on the pharmacokinetics negligible [36][37][38].…”
Section: Discussionmentioning
confidence: 97%
“…Impaired renal function was reported to affect the extent of plasma protein binding, which might affect the distribution and elimination of drugs (13,15). However, according to the U.S. Food and Drug Administration guidance (16), plasma protein binding of drugs with a relatively low extent of plasma protein binding (e.g., F u Ͼ 20%) is not markedly affected by impaired renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have demonstrated that changes in renal transporters may affect renal clearance (6,8). Additionally, abnormal plasma protein binding was reported to affect drug disposition in patients with renal impairment (13).…”
mentioning
confidence: 99%
“…Since tacrolimus largely binds to erythrocytes, anemia of CKD may cause the alteration in tacrolimus pharmacokinetics [15]. Edematous status caused by proteinuria also alters the Vd of the drug [16,17].…”
Section: Introductionmentioning
confidence: 99%